2020
DOI: 10.1016/j.fertnstert.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and objectivity of automated embryo assessments using deep neural networks

Abstract: Objective: To evaluate the consistency and objectivity of deep neural networks in embryo scoring and making disposition decisions for biopsy and cryopreservation in comparison to grading by highly trained embryologists. Design: Prospective double-blind study using retrospective data. Setting: U.S.-based large academic fertility center. Patients: Not applicable. Intervention(s): Embryo im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…Deep neural networks hold value in aiding clinical decision making and have received significant attention from the IVF community. The deep-neural network-based approach showcased here is an objective approach to one of the more subjective but important parts of a clinical IVF process-embryo selections for transfer ( Bormann et al, 2020 ). Since over 80% of fertility clinics rely on non-time lapse imaging systems as part of their clinical processes, such neural network-based algorithms that rely purely on static single timepoint images can effectively assist in decision making ( Dolinko et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep neural networks hold value in aiding clinical decision making and have received significant attention from the IVF community. The deep-neural network-based approach showcased here is an objective approach to one of the more subjective but important parts of a clinical IVF process-embryo selections for transfer ( Bormann et al, 2020 ). Since over 80% of fertility clinics rely on non-time lapse imaging systems as part of their clinical processes, such neural network-based algorithms that rely purely on static single timepoint images can effectively assist in decision making ( Dolinko et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, machine learning has been proposed as a solution for automated analysis of embryo morphologies (21)(22)(23)(24)(25)(26). This work makes use of a deep convolutional neural network (CNN), a representation learning technique, that has been proven to be effective in image classification tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bias may occur because of the wide variation in experience and skill levels of the embryologists [72]. Equally important, the variability refers to the inconsistent evaluation at a different time on the same embryo [73]. The diversity of human performance would affect the success of IVF treatment.…”
Section: A Strength Analysis For Ml-based Embryo Selectionmentioning
confidence: 99%
“…Research showed that a well-designed ML model outperformed experts in the prediction of the potential implantation of embryos [74]. The advancement of research enabled the development of MLbased applications that combine operator-independent procedure and high-processivity capabilities [73]. An ML model developed with a sufficient retrospective dataset for training a model and prognostic data features can provide reliable implantation prediction [74].…”
Section: A Strength Analysis For Ml-based Embryo Selectionmentioning
confidence: 99%